The Balance between Hydrogen Bonds, Halogen Bonds, and Chalcogen Bonds in the Crystal Structures of a Series of 1,3,4-Chalcogenadiazoles - De Silva, Viraj (Molecules, 2021)
In order to explore how specific atom-to-atom replacements change the electrostatic potentials on 1,3,4-chalcogenadiazole derivatives, and to deliberately alter the balance between intermolecular interactions, four target molecules were synthesized and characterized. DFT calculations indicated that the atom-to-atom substitution of Br with I, and S with Se enhanced the σ-hole potentials, thus increasing the structure directing ability of halogen bonds and chalcogen bonds as compared to intermolecular hydrogen bonding. The delicate balance between these intermolecular forces was further underlined by the formation of two polymorphs of 5-(4-iodophenyl)-1,3,4-thiadiazol-2-amine; Form I displayed all three interactions while Form II only showed hydrogen and chalcogen bonding. The results emphasize that the deliberate alterations of the electrostatic potential on polarizable atoms can cause specific and deliberate changes to the main synthons and subsequent assemblies in the structures of this family of compounds.